Government debt influence on EU countries economic growth: Importance of matching Maastricht criterion - Mindaugas Butkus; Kristina Matuzevičiūtė (Economic and Environmental Studies (E&ES), 2016)
The paper aims to analyse the impact of government debt on the country's economic growth. Beginning of the economic crisis in 2007 and rapid growth of government debt has attracted interest in this topic. Government debt-to-GDP ratio in the EU has increased from 58.7 to 86.8 percent from 2007 till 2014 and opened a vast field for discussions - how economic growth is affected by this situation? Using panel data approaches, we find evidence that in short-run increasing government debt has uniform negative impact on economic growth in all EU Member States but in the long-run negative impact is only in those that do not match Maastricht criterion.
Keywords: F34; H63; C23; 330; government debt; budget deficit; economic growth; Maastricht criterion